Tribological behaviour of SnO2 nanoparticles as an oil additive on brass. (8th March 2018) - Tao, Chuanlin; Wang, Bingxu; Barber, Gary C.; Schall, J. David; Lan, Huiqing
Abstract: In this research, the tribological behaviour of oil‐based SnO2 nanofluid was evaluated using flat‐on‐flat reciprocating sliding tests on brass. Oleic acid was used as surfactant to improve the stability of SnO2 nanofluid. The morphology of the worn surfaces was observed using optical microscopy, scanning electron microscopy, and energy‐dispersive X‐ray spectroscopy. It was found that oil‐based SnO2 nanofluid reduced the coefficient of friction up to 65.4% and the wear volume loss up to 43.7%. In the analysis of the chemical composition inside the wear track, a tribosintered or embedded patchy film containing tin was observed, which protected the surface against wear and lowered the coefficient of friction. The SnO2 nanoparticles might also roll or slide between 2 mating surfaces to prevent adhesive wear.